Three Spanish philosophers : Unamuno, Ortega, Ferrater Mora - Ferrater Mora, José, 1912-1991 (SUNY series in Latin American and Iberian thought and culture., 2003)
"This collection provides an excellent introduction to three of the most important names in twentieth-century Spanish philosophy: Miguel de Unamuno (1864-1936), Jose Ortega y Gasset (1883-1955), and Jose Ferrater Mora (1912-1991). The thought-provoking work of these great contemporary philosophers offers a rich and penetrating insight into human existence. Originally written by Ferrater Mora in the middle of the last century, his interpretations of Unamuno and Ortega are considered classics, and the chapter on his own thought reflects his mature thinking about being and death. Each essays in introduced by noted Ferrater Mora scholar J.M. Terricabras and contains updated biographical and bibliographic information."--Jacket